2017
DOI: 10.1016/j.rasd.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Temporal synchrony and audiovisual integration of speech and object stimuli in autism

Abstract: Background Individuals with Autism Spectrum Disorders (ASD) have been shown to have multisensory integration deficits, which may lead to problems perceiving complex, multisensory environments. For example, understanding audiovisual speech requires integration of visual information from the lips and face with auditory information from the voice, and audiovisual speech integration deficits can lead to impaired understanding and comprehension. While there is strong evidence for an audiovisual speech integration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Likewise, some researchers have found that audiovisual multisensory integration is linked to autism and related symptomatology. There is some evidence, for example, showing that metrics of audiovisual multisensory integration in individuals with ASD are correlated with language (e.g., standardized vocabulary measures; Patten, Watson, & Baranek, 2014), communication skill (e.g., communication domain score from the Autism Diagnostic Observation Schedule; Woynaroski et al, 2013a), and broader autism symptom severity (e.g., total severity score from the Social Responsiveness Scale; Mongillo et al, 2008; Smith, Zhang, & Bennetto, 2017; Turi, Karaminis, Pellicano, & Burr, 2016)…”
Section: Past Findings For Audiovisual Integration In Individuals Witmentioning
confidence: 99%
“…Likewise, some researchers have found that audiovisual multisensory integration is linked to autism and related symptomatology. There is some evidence, for example, showing that metrics of audiovisual multisensory integration in individuals with ASD are correlated with language (e.g., standardized vocabulary measures; Patten, Watson, & Baranek, 2014), communication skill (e.g., communication domain score from the Autism Diagnostic Observation Schedule; Woynaroski et al, 2013a), and broader autism symptom severity (e.g., total severity score from the Social Responsiveness Scale; Mongillo et al, 2008; Smith, Zhang, & Bennetto, 2017; Turi, Karaminis, Pellicano, & Burr, 2016)…”
Section: Past Findings For Audiovisual Integration In Individuals Witmentioning
confidence: 99%
“…However, the literature is inconclusive as to whether the multisensory TWIN in children and adolescents with ASD differs from typically developing controls. For non-speech stimuli, sometimes group differences are found (De Boer-Schellekens et al, 2013; Foss-Feig et al, 2010; Kwakye et al, 2010; Stevenson, Siemann, Schneider, et al, 2014), whereas other times they are not (Noel et al, 2017; Smith, Zhang, & Bennetto, 2017; Stevenson et al, 2017). Interestingly, two of the four studies that failed to show group differences in TWIN for non-speech stimuli, showed group differences for conditions in which speech stimuli were instead presented (Noel et al, 2017; Stevenson, Siemann, et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…The results of these two tasks were compared between the ASD and TD groups after controlling for age, sex, and intelligence quotient (IQ) and the relationships between TBW size and SIFI frequency were evaluated. Second, although some studies using other tasks containing social information have reported that altered fundamental processing (i.e., temporal and multisensory processing) affects the severity of ASD (Smith et al 2017 ; Mongillo et al 2008 ), it is unclear whether the multisensory processing performance assessed by non-social tasks (i.e., the SIFI and the flash–beep TOJ) can explain individual differences in symptom severity. Thus, the symptom severity of ASD participants was assessed and its relationships with TBW size and SIFI susceptibility were examined.…”
mentioning
confidence: 99%